Utilization of Augmented Reality as a Solution for Vernacular Language Approaches to Recognize an Object Through Speech Recognition - Arisza Zufar Fathurrahman; Dea Inesia Sri Utami; Kartika Aghni Safitri (Universitas Komputer Indonesia, 2023)
With the rise of western culture entering Indonesia, vernacular languages seem no longer essential to learn. People are more concerned with learning foreign languages and cultures so that they are relevant to the times and make it easier to adapt the professions needed, whereas preserving culture is no less important to protect the beloved country of Indonesia. Therefore, a solution relevant to the times is required to solve problems related to this vernacular language. This research aims to create a technology that will provide answers to the community to recognize the vernacular language of a particular object using Augmented Reality and Speech Recognition technology. In supporting the research, we use a qualitative descriptive method and the SDLC waterfall concept in its design. The results obtained indicate that this technology has succeeded in helping to make it easier to find out the vernacular language of an object. Augmented Reality technology gives an exciting impression when using this application. In contrast, Speech Recognition technology makes it easier for users to use this application because they can access it through speech only. With this application, people realize that preserving the vernacular language can be done using today's technology